Study of The Rate of Water Consumption per Capita in Zliten City - Khalifa, Awn Allah Salim Aoun Allah; Naji, Attia Naji (The annual Scientific Conference for Under and Postgraduate Students at the University., 2023)
The aim of this study is to study the rate of per capita water consumption in the city of Zliten because the rate of consumption is the main criterion relied upon when designing and constructing water networks feeding residential neighborhoods, taking into account the sustainability of water sources in addition to the population increase, and knowing the general awareness or lack thereof of the residents of the area. The study looks at the importance of rationalization in water consumption. The methodology of this study was based on a scientific method that relied on measuring and knowing the daily per capita consumption of water by tracking samples of houses and apartments in the city of Zliten after studying fifteen different areas. The results of the study are summarized in determining the average consumption of water per capita, as it differs in rural areas from urban areas, because in urban areas, water is supplied to the area through the water network for free in addition to the presence of a sewage network, unlike what is available in rural areas, and that this Consumption varies according to the climate. Per capita water consumption is greater in the summer than per capita water consumption in winter. It was also found that there was an increase in the consumption rate of the sample population that was chosen above the average in some other samples, and after examining and studying these samples, the reason for this was identified.
Keywords: Water consumption; Rationalization of water use; Construction of water networks; Zliten city